Simple, Efficient and Solvent-Free Method for Quantitative Regeneration of Carbonyl Compounds from Oximes by Gaseous Bromine - NAIMI-JAMAL, M.R.; SEYEDALIKHANI, M.; MOKHTARI, J. (Asian Journal of Chemistry, 2010)
Ketoximes and aldoximes are efficiently deprotected to their corresponding carbonyl compounds using bromine in the gas form under solvent-free conditions. This method is high yielding, fast, clean and more suitable for practical organic synthesis.